Urban Simulation Modeling of Aurangabad City is regarding different types of model using OPUS (Open Platform for Urban Simulation) - Sagarkumar R, Meshram; Shingne, Nilesh (International Journal of Computer Sciences and Engineering, 2025)
Many countries of the world are currently suffering from problems caused by speedily growing population in urban areas, both governments and human being have a duty to find ways to overcome these problems. We have discussed different domain of urban modeling and case study of the UrbanSim model system for Aurangabad city. Map including elementary areas of ninety nine zones in Aurangabad city and some applications for planning activities in different areas. For this work, we have used the open source software tool OPUS for urban planning and design. We have used four models, (a) Residential development project location choice model (RDPLCM), (b) Non residential development project location choice model (NRDPLCM), (c) Real estate price model (REPM) and (d) Household location choice mode (HLCM). We have done simulation using OPUS on these four models. The base year data set is the year 2012. The simulation has been performed up to the year 2022. The results for different parametric quantities have been predicted for these years. The result shows variation in population for given data set and map.